Legal Analysis Of The Increase In Divorce Cases In Indonesia With Russia As A Global Economic Impact - Ashiva Jingga; Muhammad Kadafi (Universitas Malayati, 2025)
This study aims to legally examine the correlation between global economic fluctuations, domestic economic policies, and changes in family dynamics that contribute to the surge in divorce rates in Indonesia, which reached more than 516,334 cases in 2022. The main issue raised is how global economic factors, especially those influenced by the dynamics of Indonesia-Russia economic relations, contribute to family financial instability and ultimately trigger domestic conflicts that lead to divorce. To answer the problem, this study uses a comparative legal approach, which allows the identification of legal and social factors that play a role in the increase in divorce rates The analysis is carried out by examining divorce data in Indonesia and connecting it with global economic conditions, economic crises, inflation and market uncertainty, as well as the dynamics of economic relations between countries, especially with Russia. The results of the study identified that global economic fluctuations, exacerbated by economic interactions between countries, have a significant contribution to the increase in divorce rates in Indonesia. Global economic instability has a direct impact on the economic condition of families, creating financial pressures that trigger disputes and ultimately lead to divorce. In addition, this study also analyzes the legal implications of this phenomenon, highlighting how existing laws respond to and handle divorce cases triggered by economic factors. Based on these findings, this study concludes that global economic stability has an important role in maintaining the integrity of families in Indonesia. Economic fluctuations that have an impact on the family's financial condition can be the main trigger for conflict and divorce. Furthermore, the dynamics of international economic relations, as exemplified in Indonesia-Russia relations, can strengthen or weaken the impact of the global economy on families in Indonesia. Therefore, this study suggests the need for adaptive and responsive economic policies to global dynamics, with a focus on strengthening the family economy and social protection. In addition, it is also necessary to strengthen regulations and law enforcement in favor of families affected by the economic crisis, as well as pre-marital and post-marriage mediation and counseling programs that focus on family financial management and conflict resolution